Mulheres que habitam em mim: um olhar sobre o feminino ancestral familiar como fio indutor para experiências de imersão e emersão em dança - ARAÚJO, Thays Amanda Mesquita de (2023)
This article is the result of the course completion work organized in accordance with Normative Instruction No. 01/2023 PROEG/UFPA, which makes exceptional and temporary provision for academic guidelines for the standardization and performance of Course Completion Work - TCC activities, making its preparation, presentation and defense more flexible, due to the consequences resulting from the COVID-19 pandemic; with regard to Art.4, paragraph I, which concerns the preparation of a scientific article. Considering this, this work presents the beginning of a creative process that involved writing experiences (Evaristo, 2018) based on immersion and emersion experiences in dance (Souza,2022) entitled "TRÍADE OF ANCESTRAL MEMORIES", which pointed to three developments, namely: memories of blessing with my mother; childhood memories and games in the igarapés and memories of blessing in my grandmother's yard. The aim of the research was to reaffirm my Afro indigenous,peripheral body, daughter of Yabá, artist, from the perception of the power of the different feminizes that make up my ancestral life and artistic trajectory. therefore, this article is based on writings as a theoretical-methodological guideline based on Evaristo (2018) and Soares (2017) regarding the realization of experimentation. for creative processes in dance, the concept of EIES (immersion and emersion experiences) was based on Souza (2022), in addition to important references such as: Oliveira and Cunha (2022), Martins (2003), among other authors. the results of this research, therefore, revealed the importance of reaffirming and giving visibility to Afro-indigenous female family ancestral memories as an inductive thread for creation processes as a practical field of knowledge, expressions and subjectivities of resistance that also contribute to their epistemes as a field of knowledge and doing in dance research.